Internationalization of e-commerce corporations (ECCs): Advanced vs emerging markets ECCs. Issue 4 (22nd November 2018) - Benmamoun, Mamoun; Singh, Nitish; Lehnert, Kevin; Lee, Sang Bong
Abstract : Purpose: The growth of global e-commerce presents significant opportunities for global expansion. Yet it has not leveled the playing field between emerging markets e-commerce corporations (EM-ECCs) and advanced markets ECCs (AM-ECCs). While AM-ECCs have been expanding overseas with considerable success, EM-ECCs have been less disposed to internationalize and have been content to serve and defend their home turfs against foreign rivals who wield monopolistic advantages. Leveraging the network, ownership, location and internalization (N-OLI) theoretical framework, this paper aims to examine the variables affecting the internationalization of AM-ECCs and EM-ECCs. Design/methodology/approach: This paper adopted an exploratory research method using multiple corporate cases to focus on understanding the dynamics present within single settings, capture corporate context and allow comparison between cases. Findings: The findings suggest that AM-ECCs, in comparison to EM-ECCs, are endowed with favorable and strong network-based advantages, ownership-based advantages, location-based and internalization-based advantages that make them more capable of pursuing internationalization aggressively. However, EM-ECCs are induced to pursue regionally-focused internationalization due, on the one hand, to capital scarcity, weaknesses on network-based and internalization-based advantages and, on the other hand, to geographical strength and strong location-based advantages emanating from knowledge of the home region. Originality/value: This paper identifies the internationalization challenges that EM-ECCs face with respect to AM-ECCs. While extending the theoretical discussion of the N-OLI framework in light of EM-ECCs, this paper also extends the EM-ECC strategies within local and regional markets, including emerging markets such as India and the Middle East. This extension supports the assertion that regional focused strategies are not immune to technological advantages which support the notion of a regional strategic growth strategy because of localization advantages and capital leverage limitations. Finally, the paper expands the analysis to some emerging markets that have attracted less attention in the literature, namely, India and the Middle East.